STAD and NHT Learning Application in Class VIII Social Science Subjects of SMP Negeri 1 Tompaso - Lempas, Jety Deisye (Technium Social Sciences Journal, 2022)
This study aims to determine the differences between student learning outcomes taught by applying the STAD learning model and the NHT learning model in social science subjects, Class VIII. This research was conducted at SMP Negeri 1 Tompaso using an experimental method with two treatments and two experimental classes, one class using the STAD learning model and one class using the NHT learning model which was taken randomly. The variables in this study are: (i) student learning outcomes obtained using the STAD learning model (X1) and (ii) student learning outcomes obtained using the NHT learning model (X2). Data were analyzed with descriptive statistics followed by t-test mean difference. The results showed that the STAD and NHT learning models can (i) increase the average student learning outcomes, namely 84.46 for STAD and 85.00 for NHT and (ii) increase the percentage of students who have scored to meet the MCC, namely 96.4 % for STAD and 92.90% for NHT. The average student learning outcomes are not significantly different between the STAD and NHT learning models. Both of these learning models are suitable for use in social science subjects of class VIII